(untitled) (Journal of Digital System Development, 2025)
Malaysia is ranked 10th globally for the highest number of smartphone users, with around 24 million users. Every student in higher education institutions owns a self-purchased or government-provided smartphone. The advancement in facilities necessitates a comprehensive transformation, especially in education. Traditional teaching methods using thick, costly notebooks are burdensome and outdated. Therefore, researchers and colleagues have developed an Islamic Studies Made Easy (IsMe) smartphone application for students taking Islamic Studies courses. To determine the effectiveness of this application, a study was conducted on polytechnic students enrolled in Islamic Studies courses using quantitative methods by distributing questionnaires to 67 respondents. The study’s findings indicate that students are more interested in learning Islamic Studies because it is easier to refer to, discuss with lecturers, and save costs using the developed IsMe application. For improvement, the researchers must address non-Android users’ inability to download the application. In conclusion, these findings indicate the need for 21st-century learning that leans towards using information technology in teaching and learning, aligning with the IR 4.0 education revolution.